The Role of Pentecostal Church Leadership to the Covid 19 Pandemic in Zimbabwe (Global Journal of Management and Business Research, 2021)
Pentecostal churches in Zimbabwe have large number of followers and these were also affected by the Covid 19 pandemic which has been and is still torturing the entire world These churches have leadership structures at differentlevels ranging from national to smaller groups of an assembly There is need to understand the roles played by leadership at different levels in fighting against the pandemic in Zimbabwe The study used an online survey to reach out to leaders and learn their efforts in managing the Covid 19 pandemic The survey got insights into encounters of the leaders with the pandemic as well as different roles which they played in managing both the virus and their members
Keywords: pentecostal churches; covid 19; pandemic; lockdown; world health organization; zimbabwe; health